Effect of Illuminance Transition Rate on Survival of Juvenile Pacific Bluefin Tuna, Thunnus orientalis. Issue 5 (October 2014) - Honryo, Tomoki; Kurata, Michio; Okada, Tokihiko; Sawada, Yoshifumi; Ishibashi, Yasunori
Abstract To investigate the reason for the high mortality of cultured juvenile Pacific bluefin tuna (PBT), especially during land‐based culture, we examined the effect of the rate of light‐intensity change during the dawn period. Juvenile PBT kept in a natural light environment (control) were compared with those exposed to an artificially slowed change in light intensity during the dawn period (test group). For the test group, lamps, which were connected to automatic timers and placed above the rearing tank, were switched on from 0345 to 0515 h at 15‐min intervals. After 9 d, the survival rate of the test and control group was identical. Between Day 1 and Day 6, whole‐body cortisol levels were not different between groups. However, whole‐body glucose levels in the test group were significantly higher than those in the control group. Both groups displayed a diel rhythm in plasma cortisol concentration that peaked at 0300–0600 h. These results suggest that slowing the increase in light intensity during the dawn period did not improve survival and that low light intensity itself induces high mortality in cultured PBT juveniles.